Model of Interreligious Harmony Based on Local Wisdom as a Means of Conflict Prevention: a Case Study of The Peaceful and Culturally-Oriented Village Of Nglinggi, Klaten, Central Java - Augustine, Helin Candra; Setiawibawa, Rachmat; Uksan, Arifuddin; Sagala, Parluhutan (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2025)
This study aims to explore the model of interreligious harmony in Nglinggi Village, Klaten, Central Java, which is rooted in local wisdom, and to examine its role as a means of preventing social conflict. Nglinggi Village, known for its religious diversity, has earned recognition as a Culturally Peaceful Village due to the community’s various efforts to foster harmony. This research employs a descriptive qualitative approach using a case study method. Data were collected through participatory observation, in-depth interviews with religious and community leaders, and documentation studies of interreligious harmony activities. The findings indicate that local cultural traditions such as gotong royong (mutual cooperation), sadranan (ancestral commemoration), and sharing practices during religious holidays play a crucial role in sustaining long-term harmony. Local wisdom in Nglinggi Village serves as an effective model for preventing social conflict in plural societies. This study is expected to contribute to the development of culturally based peacebuilding efforts in Indonesia.